2013
DOI: 10.1103/physrevb.88.041108
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigation of the diluted magnetic semiconductor Li(Zn1xMnx)P (x=

Abstract: We employ NMR techniques to investigate the nature of Mn spins in the I-II-V diluted magnetic semiconductor Li(Zn1−xMnx)P (x = 0.1, Curie temperature Tc = 25 K). We successfully identify the 7 Li NMR signals arising from the Li sites adjacent to Mn 2+ , and probe the static and dynamic properties of Mn spins. From the NMR spin-lattice relaxation data, we show that the Mn spin-spin interactions extend over many unit cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 25 publications
1
50
0
2
Order By: Relevance
“…It has been shown from NMR20 and μ SR measurements that the ferromagnetism in (BaK)(ZnMn) 2 A s 2 9, Li(Zn, Mn)As10, (La, Ba)(Zn, Mn)AsO12 and Li(Zn, Mn)P21 are homogeneous, i.e., the long range ferromagnetic ordering is arising from the Mn atoms doped at Zn sites, instead of Mn related magnetic impurities. Furthermore, μ SR results demonstrated that these bulk form DMSs share the same mechanism for the ferromagnetic ordering as that of (Ga, Mn)As22.…”
mentioning
confidence: 99%
“…It has been shown from NMR20 and μ SR measurements that the ferromagnetism in (BaK)(ZnMn) 2 A s 2 9, Li(Zn, Mn)As10, (La, Ba)(Zn, Mn)AsO12 and Li(Zn, Mn)P21 are homogeneous, i.e., the long range ferromagnetic ordering is arising from the Mn atoms doped at Zn sites, instead of Mn related magnetic impurities. Furthermore, μ SR results demonstrated that these bulk form DMSs share the same mechanism for the ferromagnetic ordering as that of (Ga, Mn)As22.…”
mentioning
confidence: 99%
“…The NMR and µSR measurements confirmed that the ferromagnetism in these bulk DMSs is homogeneous. 11,18,20,29 In this article, we report the successful synthesis and characterization of a new DMS with co-doped both Co and Mn into the same Zn sites of LiZnAs. With Co and Mn simultaneously substitution for Zn sites, the system exhibits ferromagnetic order up to 40 K. The influence of Co and Mn concentration on the ferromagnetic ordering state is discussed in detail in this work.…”
Section: Introductionmentioning
confidence: 99%
“…After this discovery, several new types of bulk forms of DMSs with decoupled spins and charges injections have been reported. [17][18][19][20][21][22][23][24][25][26][27] The availability of bulk forms of specimens make it possible to investigate the microscopic magnetism of DMSs based on typical bulk probes, 28 such as nuclear magnetic resonance (NMR), 29 muon spin relaxation (µSR), 17,18,20,30 neutron scattering, absorption spectroscopy (XAS), 31 resonance photoemission spectroscopy (RPES), 31 and angle-resolved photoemission spectroscopy (ARPES). 32 It has been confirmed by the XAS measurements that the valence of Mn in (Ba,K)(Zn,Mn) 2 As 2 is bivalence.…”
Section: Introductionmentioning
confidence: 99%
“…The strong electron-phonon coupling in molecular junctions can lead to the polaronic regime in which electronic states are dressed by phonon cloud 32,33 . The polaronic effect exhibits novel transport properties, such as negative differential conductance 27,34,35 , phonon-assisted current steps [35][36][37][38][39][40] , Franck-Condon blockade [39][40][41] , sign change in the shot noise correction 42 , and etc.. Rectification effect of electric current in a single molecular dimer, which is modeled as a DQD with strong polaron effect, has been reported 43 , while the thermal rectification counterpart is yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%